Implementasi Metode Inkuiri dalam Pembelajaran Al-Qur’an Hadist Materi Hukum Bacaan - Nurdianty, Erika Khusnul; Mansur (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
This study aims to determine the inquiry method in learning al-Qur'an Hadith, especially in the material of the law of reading at MTs Negeri 1 Karanganyar and MTs Negeri 8 Sragen in 2022, the obstacles faced in the application of the inquiry method of learning al-Qur'an Hadith in the material of the law of reading at MTs Negeri 1 Karanganyar and MTs Negeri 8 Sragen in 2022 and to find out the solutions carried out in learning al-Qur'an Hadith in using the inquiry method of reading law material in 2022. This research is a descriptive qualitative research using data analysis. The data in this study were obtained through interviews, observation and documentation. Based on the results of this study indicate that the implementation of learning using the inquiry method runs smoothly. The implementation of learning in applying the inquiry method is the implementation of activities consisting of six stages including: orientation, formulating problems, formulating hypotheses, summarizing data, testing hypotheses and formulating conclusions. The obstacles faced in learning al-Qur'an Hadith using the inquiry method at MTs Negeri 1 Karanganyar and MTs Negeri 8 Sragen are in the division of groups and material regarding reading laws, especially “mad” material, students do not understand it when directly directed to look for themselves in the Qur'an, maybe globally children can still do it. The solutions carried out by teachers in learning al-Qur'an Hadith reading law material with the inquiry method at MTs Negeri 1 Karanganyar and MTs Negeri 8 Sragen include teachers making peer tutors, giving more practice questions and tasks to find reading laws in the Qur'an according to the material taught so that students were learning by practicing it directly in the Qur’an.